The Influence of Market Penetration Strategies on Market Share in the Hospitality Industry in Arusha, Tanzania (International Journal of Scientific Research and Management (IJSRM), 2022)
Organizations must implement competitive product-market strategies to secure their survival and sustainability in the marketplace. They must surpass competitors that follow other generic strategy types or those who are trapped in the middle. Although several investigations have been carried out in the tourist sector, none have been conducted on the marketing methods employed by Tanzanian tour firms. The purpose of the research was to see if companies are still using Igor Ansoff’s product-market strategies to grow their market share. The main purpose of this study was to determine the impact of market penetration strategies on Arusha-based travel companies’ expansion of market share A survey research design was employed in the study, targeting marketing managers from tour companies in Arusha. To determine the sample size, the researchers utilized basic random sampling. The data was gathered from a sample of 44 people. The marketing managers were handed a questionnaire with 17 questions to complete. Quantitative techniques were used to analyze the information gathered. When the data was acquired, it was cleaned, coded, categorised, and sorted. Information was then computed both by computations of deductive and expressive nature. Results indicate that market penetration strategy (β = .732, p = .000<.05) significantly influences market share at 95% confidence level. The study therefore concludes that market penetration strategy significantly influences market share among tour companies in Arusha, Tanzania. It is recommended in addition to sustaining and improving current practices under the strategy, tour companies in the country ought to continue to embrace the market penetration strategy.